Assessing the impact of long-term inhaled corticosteroid therapy on patients with COVID-19 and coexisting chronic lung disease: A multicenter retrospective cohort study - Adela Pina Belmonte; Manuel Madrazo; Laura Piles; Manuel Rubio-Rivas; Lucía de Jorge Huerta; María Gómez Antúnez; Juan Francisco López Caleya; Francisco Arnalich Fernández; Martin Gericó-Aseguinolaza; Paula Maria Pesqueira Fontan; Nicolás Rhyman; Marina Prieto Dehesa; et al. (Canadian Journal of Respiratory Therapy)
# Background